Basics of chimeric antigen receptor (CAR) immunotherapy - Balkhi, Mumtaz Yaseen (Academic Press, 2020)
Basics of Chimeric Antigen Receptor (CAR) Immunotherapy presents the latest on how T cell adoptive immunotherapy has progressed in its ultimate goal of curing metastatic malignant cancers. Recent clinical data obtained with checkpoint receptor blockade inhibitors and chimeric antigen receptor (CAR) therapy has been especially promising, thus generating renewed hope that we may be on the verge of finally curing cancer. Over the years, huge progress has been made in controlling several stage IV metastasized cancers through the clinical application of checkpoint receptor inhibitory drugs and CAR-Therapy that has seen unprecedented interest in the immunotherapy field.